2022
DOI: 10.1155/2022/6804155
|View full text |Cite
|
Sign up to set email alerts
|

Shear Performance of Concrete Beams with a Maximum Size of Recycled Concrete Aggregate

Abstract: e use of concrete mixes with recycled materials has gained traction in research communities. However, the major drawback of the recycled concrete aggregate (RCA) has been the contribution of the cement paste mortar attached to the surface. e quantity of surface-attached mortar on the virgin aggregate dominates and de nes the shear performance of concrete beams. Concrete shear failure is usually abrupt and catastrophic, especially in concrete beams without shear reinforcement. e e ectiveness of the maximum size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Their surfaces were then coated for an hour with sodium metasilicate pentahydrate solution. B. Ordo et al [186] used the application to structural concrete beams without shear stirrups, which will be guided by the pozzolanic preparation with slurry-containing cement and RHA for the ideal coarse RAC size. This work also suggests a surface treatment mechanism for RACs use a targeted strategy to improve the physical and mechanical characteristics of the aggregate to enhance aggregate performance in beams.…”
Section: Shear Behavior Of Rac and Trac Beamsmentioning
confidence: 99%
“…Their surfaces were then coated for an hour with sodium metasilicate pentahydrate solution. B. Ordo et al [186] used the application to structural concrete beams without shear stirrups, which will be guided by the pozzolanic preparation with slurry-containing cement and RHA for the ideal coarse RAC size. This work also suggests a surface treatment mechanism for RACs use a targeted strategy to improve the physical and mechanical characteristics of the aggregate to enhance aggregate performance in beams.…”
Section: Shear Behavior Of Rac and Trac Beamsmentioning
confidence: 99%
“…The usage of recycled concrete aggregates has been used in concrete members for the last several years, and its effect on the shear strength of the concrete beams has been investigated by several research teams lately. Odero et al [21] tested sixteen concrete beams using RCA and concluded that at 10 mm aggregates, the shear capacity of the specimens was at its highest by 21.5%. Sagheer et al [22] had tested fifteen concrete beams with 50 % RCA for some and 100 % RCA for the others.…”
Section: Introductionmentioning
confidence: 99%
“…(M/ Vd) still has physical signifcance at any cross-section of a beam. In addition, Brian et al [9] showed that regardless of the kind of the coarse aggregate material employed, the shear span-to-depth ratio was found to signifcantly infuence the shear strength of beams. Because continuous beams constitute the majority of the actual construction, understanding the efect of continuity on shear behavior is critical.…”
Section: Introductionmentioning
confidence: 99%
“…(9) Te values for the ACI equation became less conservative as a/d increased; the fexural moment might have had something to do with this.…”
mentioning
confidence: 99%